2018
DOI: 10.1111/age.12637
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of effects of heterozygosity in dairy cattle for bovine tuberculosis resistance

Abstract: SummaryGenetic selection of cattle more resistant to bovine tuberculosis (bTB) may offer a complementary control strategy. Hypothesising underlying non‐additive genetic variation, we present an approach using genome‐wide high density markers to identify genomic loci with dominance effects on bTB resistance and to test previously published regions with heterozygote advantage in bTB. Our data comprised 1151 Holstein–Friesian cows from Northern Ireland, confirmed bTB cases and controls, genotyped with the 700K Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…Nonetheless, consistency is lacking in genomic studies on bTB infection in the regions of the genome putatively associated with bTB infection. For example, putative quantitative trait loci (QTL) pertaining to bTB infection in Holstein cattle have been reported on BTA1 [10], BTA2 [5], BTA6 [11], BTA13 [5], BTA22 [12], and BTA23 [7,10]. Even when the same autosome was documented in two studies for association with bTB [7, 10], the QTL identified to harbor putative single nucleotide polymorphisms (SNP) by Richardson et al [7] were 28 Mb downstream of the QTL identified on the same autosome by Raphaka et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, consistency is lacking in genomic studies on bTB infection in the regions of the genome putatively associated with bTB infection. For example, putative quantitative trait loci (QTL) pertaining to bTB infection in Holstein cattle have been reported on BTA1 [10], BTA2 [5], BTA6 [11], BTA13 [5], BTA22 [12], and BTA23 [7,10]. Even when the same autosome was documented in two studies for association with bTB [7, 10], the QTL identified to harbor putative single nucleotide polymorphisms (SNP) by Richardson et al [7] were 28 Mb downstream of the QTL identified on the same autosome by Raphaka et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…Amos et al (2013) investigated a possible effect of a particular TB genotype, which was noted to be prevalent in non-reactor animals. Increases in skin thickness were lower in animals with the "22" genotype [21], although a subsequent study investigating the same genomic region in a larger dataset did not find any evidence to support these findings [22]. It was also observed that the difference in skin thickness between the bovine tuberculin site and avian tuberculin site was reduced in animals pre-exposed to Mycobacterium avium [23].…”
Section: Discussionmentioning
confidence: 97%
“…bovis infection resistance in domestic cattle (Raphaka et al 2017;Tsairidou et al 2018a;Tsairidou et al 2018b;Ring et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel to functional genomics studies of bTB, increasingly powerful genome-wide association studies (GWAS) have been performed in Irish and UK cattle populations using estimated breeding values (EBVs; estimate of genetic merit of an animal derived from a statistical model) for several M. bovis infection resistance traits with heritabilities ranging from 0.04 to 0.37, depending on the phenotype used (Finlay et al 2012;Bermingham et al 2014;Richardson et al 2016;Raphaka et al 2017;Wilkinson et al 2017;Tsairidou et al 2018b;Ring et al 2019). These GWAS have used medium-and high-density single-nucleotide polymorphism (SNP) arrays and, more recently, imputed whole-genome sequence (WGS) data sets for a large multi-breed GWAS on 7,346 bulls, which identified 64 quantitative trait loci (QTLs) associated with resistance to M. bovis infection (Ring et al 2019); the association study was based on phenotypic data from 781,270 individuals.…”
Section: Introductionmentioning
confidence: 99%